The Effect Of Magnetized Castor Oil Biodiesel Blended With Petrodiesel Fuel On Engine Performance And Emission Characteristics - Sisay, Suyume (ASTU, 2020)
The Purpose Of This Study Is To Experimentally Investigate The Engine Performance And Pollutant Emission Of A Commercial Si Engine Using Ethanol??Methanol And Gasoline Blended Fuels With Various Blends (E10%, M2% And G88% Respectively). Removing The Biomass Limit Is One Of The Great Challenges To Further Enlarge The Share Of Renewable Ethanol As Alternative For Fossil Fuels. One Of The Possible Solutions For This Constraint Is The Ternary Gem (Gasoline-Ethanol-Methanol) Blends. Our Project Studies Are Going To Find A Suitable Alternate Fuel, To Reduce The Exhaust Emission Level. If The Methanol Is Produced Out Of Renewable Sources, These Blends Can Help Extend The Part Of Clean Fuels On The Market. The Development Of A Tri-Fuel Vehicle, Capable Of Operating On Any Combination Of Gasoline, Ethanol, And Methanol, Using A Single Fuel System Is Described, Demonstrating That Compatible, Affordable Transport Can Be Developed, Supplied By Sustainable Organic Fuels. The Results Were Compared To Performance Of Engine From Use Of Regular Gasoline. The Vehicle Was Tested For Brake Power, Brake Torque And Brake Specific Fuel Consumption Using Chassis Dynamometer. The Performance Tests Were Conducted Using Chassis Dynamo Meter On A Vehicle Equipped With A Four Cylinder Production Spark Ignition (Si) Engine, Without Any Major Modifications Of Hardware To Investigate The Comparative Performance Characteristics Of The Gasoline, Ethanol-Gasoline And Methanol-Ethanol-Gasoline Mixtures. There Is A Better Brake Torque Performance At The Range Of 25-30 Km/Hr When Compared To Gasoline. At Medium Speeds There Is A Reduction In Torque Compared To Gasoline, But It Is Similar With Gasoline-Ethanol Blend. The Brake Power Of Methanol-Ethanol-Gasoline Is Higher Than Gasoline & Ethanol-Gasoline When The Vehicle Is Driving At Medium Speed Especially At 45 - 50 Km/Hr At 3 Rd Gear. The Brake Specific Fuel Consumption (Bsfc) Result Shows That The Performance Of The Gasoline-Ethanol-Methanol Blend Is Better Than Gasoline & Gasoline-Ethanol Blend.
Keywords: biodiesel, castor oil, magnetization, transesterification, performance and emission